2011
DOI: 10.1175/2011jas3614.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Factors Modulating the Stratocumulus to Cumulus Transitions

Abstract: Large-eddy simulation (LES) is used to explore the role of various processes in regulating the stratocumulus to cumulus transition (SCT). Simulations are based on a composite case derived from a Lagrangian analysis of 2 yr of data from the northeastern Pacific. The simulations reproduce well the observed transition from a compact stratocumulus layer to more broken fields of cumulus, simply as a response to increasing sea surface temperatures (SSTs) along the transition. In so doing they support earlier theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
231
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(252 citation statements)
references
References 26 publications
21
231
0
Order By: Relevance
“…Because meteorology and aerosol typically covary in somewhat predictable ways, neither of the methods is a realistic sampling of what the atmosphere presents (30) is used to simulate a transition case in the presence of (absorbing) smoke aerosol residing some distance above, and later entrained into cloud. Forcings, including a gradual increase in sea surface temperature, are applied (30). For this transition case, the SW heating associated with the aerosol is also coupled to dynamics (31).…”
Section: Resultsmentioning
confidence: 99%
“…Because meteorology and aerosol typically covary in somewhat predictable ways, neither of the methods is a realistic sampling of what the atmosphere presents (30) is used to simulate a transition case in the presence of (absorbing) smoke aerosol residing some distance above, and later entrained into cloud. Forcings, including a gradual increase in sea surface temperature, are applied (30). For this transition case, the SW heating associated with the aerosol is also coupled to dynamics (31).…”
Section: Resultsmentioning
confidence: 99%
“…This provides a framework for systematically comparing LES responses with those of climate models in which the above forcings change in model-dependent and location-dependent ways as climate warms. It could also help integrate results from a small but growing set of LES studies investigating the response of different types of cloudtopped boundary layers to different types of forcing perturbations possibly relevant to climate change [e.g., Blossey et al, 2009;Lock, 2009;Xu et al, 2010;Sandu and Stevens, 2011;Nuijens and Stevens, 2012;Rieck et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Myers and Norris (2013) corroborated this finding by showing from observations that low cloud amount in the subtropics tends to decrease as subsidence becomes stronger. Moreover, Sandu and Stevens (2011) performed several LESs of stratocumulus transition cases and found that although the entrainment rate increased in the sensitivity run with reduced subsidence, the larger entrainment drying and warming trend of the boundary layer did apparently not lead to a more rapid cloud break up. To shed some light on this finding, a budget equation for the tendency of the LWP of the stratocumulus layer as derived by Van der Dussen et al (2014) is used to analyze results of idealized LESs in order to determine the role of each individual physical process during stratocumulus transitions.…”
Section: Introductionmentioning
confidence: 99%